Beat Death. Anthropological and Theological Critique of Transhumanist Project - Justo Domínguez, Emilio-José (Logos. Anales del Seminario de Metafísica, 2020)
The transhumanist movement has, among its main proposals, the project to extend the lifespan in order to achieve immortality in an indefinite life or in a cybernetic way of existence. This article presents the proposal of transhumanism and reflects on the desire to be immortal and the anthropological implications of death. Criticism is made from the consideration of fundamental aspects of the human being, such as finitude, historicity and vulnerability. In adittion, the transhumanist project of conquering death implies a proposal for salvation, which coincides in its formulation with the same that Christianity does. Both claim a victory over death. Theological criticism focuses on the understanding of death and the reflection on the means to overcome it. In this article, the criticism of the transhumanism project is directed, rather than what it proposes, to what remains without raising, causing a reduction in the understanding of death and the way to beat it.
Keywords: death; finitude; historicity; inmortality; lifespan; redemption; relationality; resurrection; vulnerability